Biological Properties Of Benzopyran-Based Platinum (Ii) Complexes - Malinowska, Katarzyna; Modranka, Roman; Majsterek, Ireneusz; Misiak, Piotr (Polski przeglad chirurgiczny, 2014)
The aim of the study was to analyze the physicochemical synthesized complex 3 [(1,3- thiazol -2- ylimino) methyl)]-4H- chromene -4 -one with tetrachloroplatinate(II) dipotassium and determination peroxidase activity and glutathione (GPX) in red blood cells of cancer patients and healthy subjects. Materials and methods. Tests were carried out with the approval of the Bioethics Committee No. RNN/260/08/KB. Blood was collected into tubes with anticoagulant (heparin lithium). Determination of glutathione peroxidase activity was performed by methods of Little and O’Brien in 20 person groups hospitalized at the Department of General and Colorectal Surgery Veterans General Hospital in Łódź. Results. The study was an increase of activity in the control without the compound and after the introduction of the complex relative to the treatment groups. In healthy subjects, without the use of glutathione peroxidase complex averaged 73.25 ± 23.88 U / g Hb after application of the compound corresponds to the reference group 81.01 ± 25.94 U / g Hb. In contrast, in patients without the use of the complex activity amounted to 42.85 ± 27.49 U / g Hb. In the study group, which uses synthesized complex GPX activity corresponds to 67.72 ± 13.44 U / g Hb. Conclusions. The obtained results underline that the introduction of significant blood antioxidant complex research has a significant impact on the results of the determinations. Statistically significant (p < 0.05) difference occurred in both test and no relation to the administration of the complex in relation to the control of 1. 2.